2020
DOI: 10.3390/nano10020314
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Gold–Ceria Nanoparticles: Superior Optical Fluorescence Quenching Sensor for Dissolved Oxygen

Abstract: Cerium oxide (ceria) nanoparticles (NPs) have been proved to be an efficient optical fluorescent material through generating visible emission (~530 nm) under violet excitation. This feature allowed ceria NPs to be used as an optical sensor via the fluorescence quenching Technique. In this paper, the impact of in-situ embedded gold nanoparticles (Au NPs) inside ceria nanoparticles was studied. Then, gold–ceria NPs were used for sensing dissolved oxygen (DO) in aqueous media. It was observed that both fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…6d. The calculated K sv is 1334.83 M −1 in this work, which is considerably higher than 893.7 M −1 and 454.6 M −1 of previously reported Au-ceria NPs 14 and Al-ceria NPs 49 fluorescence sensing materials. Furthermore, the fitting results show that the detection sensitivity of ZNS-2 to DO in this study was 0.036 mg L −1 , which is higher than that of the other sensing materials used in the literature listed in Table 1.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…6d. The calculated K sv is 1334.83 M −1 in this work, which is considerably higher than 893.7 M −1 and 454.6 M −1 of previously reported Au-ceria NPs 14 and Al-ceria NPs 49 fluorescence sensing materials. Furthermore, the fitting results show that the detection sensitivity of ZNS-2 to DO in this study was 0.036 mg L −1 , which is higher than that of the other sensing materials used in the literature listed in Table 1.…”
Section: Resultscontrasting
confidence: 53%
“…Shehata et al reported gold-ceria nanoparticles for DO detection. 14 The results indicated that optical coupling between the fluorescence emission of ceria and the plasmon resonance on the surface of gold nanoparticles could improve the sensitivity of gold-ceria nanoparticles for DO detection, with a Stern-Volmer constant of 893.7 M À1 . However, the high price of gold is not conducive for practical applications.…”
Section: Introductionmentioning
confidence: 97%
“…The GNP-based pregnancy test to detect urinary human chorionic gonadotropin (hCG) went on the market in the 1980s [6,7]. Owing to excellent optical and electrical properties, GNP and its composites are frequently used to develop sensing devices [8][9][10] and diagnostic kits [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Collisional quenching [16][17][18][19][20] between oxygen molecules and fluorescence or phosphorescence molecules in a support matrix is the basis for most optical fiber DO sensors. It has been demonstrated that optical fiber chemical sensors have superiorities over other DO sensors, such as ease of operation, cost-effectiveness, and anti-electromagnetic interference.…”
Section: Introductionmentioning
confidence: 99%